SPEED CONTROL OF A BDFRM DRIVE BY USING MODEL PERIDECTIVE CURRENT CONTROL TECHNIQUE - P. A. Prabhakara; S. Shridhar; A.Aruna (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Model predictive control (MPC) is now considered an effective control approach for achieving accurate and rapid drive control. Model predictive control the voltage vectors needs to assessed in control objectives defined in terms of power, current, flux, andtorque. An iterative prediction loop, for choosing the best optimal one for the following control interval. Easy to implement Model Predictive Control and shows obvious unique execution, but in the steady state performance is hampered to thevoltage vectors areavailable in limited range, mainly in two-level voltage-source-inverters.The purpose of this project is to investigate the viability of the Model predictive control approach for a fresh student, a BDFRM drive, using thecontrol variable is secondary current. In addition, the duty-cycle control approach is used to address the issue of steady-state inferiorityBy replacing the inner current proportionalintegral (PI) controllers and pulse-width modulator with an optimization-based model predictive current controller. In contrast to the suggested work, extensive MATLAB simulation analysis was performed.